SOCIAL VULNERABILITY, RURALITY, AND EMERGENCY COLON CANCER CARE: A NARRATIVE REVIEW - Michał Babicz; Oliwer Muller; Katarzyna Rosa; Agata Słoma; Jagoda Pałubska; Natalia Malatyńska; Anna Szot; Dominik Szydełko; Daria Danielczyk; Paweł Żurek (International Journal of Innovative Technologies in Social Science, 2026)
Objective: To integrate recent evidence on the ways neighborhood social vulnerability and rural residence influence emergency presentation in colon cancer and the care trajectory that follows surgery. Methodology: This narrative review examined PubMed-indexed literature identified through a targeted search on March 5, 2026. Systematic reviews, multicenter observational studies, and intervention studies published in English between 2013 and 2026 were prioritized, with preference for colon-specific evidence and selective inclusion of colorectal studies when directly applicable to colon cancer pathways. Results: The literature points to a consistent pathway: socially vulnerable and rural populations are screened less often, enter care later, undergo non-elective surgery more frequently, and face greater difficulty completing postoperative and adjuvant care. Studies also suggest that provider availability, Commission on Cancer accreditation, patient navigation, and telehealth-supported follow-up can mitigate part of this disadvantage, although digital strategies remain constrained by broadband access, language barriers, and digital literacy. Conclusion: Emergency colon cancer surgery is best interpreted as a downstream marker of inequity across the care continuum. Efforts to reduce it should connect public-health outreach, access planning, perioperative care, and technology-enabled continuity rather than treating the emergency operation as an isolated event.